Positional contrasts in key techniques between men's and women's basketball at the Olympic level - Zhang, Yihong; Wang, Jie; Tan, Shi (Frontiers in Sports and Active Living, 2025)
This study aims to indentify the key techniques of role players at each position in the Olympic basketball games, contrast the differences in key technique performance between men’s and women’s basketball players at the different positions, and explore the factors that lead to the differences in technique performance. Comprehensive offensive and defensive technique data were systematically recorded across 52 games during the 2024 Olympic Games. CatBoost algorithm was subsequently implemented to identify key techniques through feature importance analysis. Results showed that the key techniques for men guards were 2PM, 3PM, AST, One-hand Pass, and BLK. The key techniques for women guards were Two-hand Pass, AST, 2PM, 3PM, and ORB. The key techniques for men forwards were Two-hand Pass, 2PM, FTM, 3PM and One-hand Pass. The key techniques for women forwards were 2PM, DRB, Dribble penetration, Two-hand Pass, and One-hand Pass. The key techniques for men’s centers were defensive rebounds DRB, 2PM, One-Hand Pass, AST, and 3PM. The key techniques for women centers were Two-hand Pass, One-hand Pass, FTM, BLK, and DRB. This study suggests that basketball coaches should design different training methods and competition strategies for players in different positions.